Multi-Parameter Optimization for the Wet Steam Accumulator of a Steam-Powered Catapult - Zhu, Qidan; Lu, Peng; Yang, Zhibo; Ji, Xun; Han, Yu (Energies (Basel), 2019)
Selecting the optimal parameters for wet steam accumulator of steam-powered catapult is an important task, due to launching safety. There is no literature on the topic of the parameters optimization for wet steam accumulator of steam-powered catapult. The genetic algorithm (GA) was used to determine the optimal wet steam accumulator in this article. The sink-off-the-bow (SOB), angle of attack and rate of climb were used to create the objective function. The multi-objective optimization can be converted to single-objective optimization, which is subject to angle of attack and rate of climb. Moreover, the simulation model of the steam catapult system was built by creating a thermodynamics model of steam-powered catapult, a mathematical model of traction release device, a statics model of tensioning, a statics model of full takeoff power, a mathematical model of catapult force build-up with holdback, a model of release, a dynamics model of power stroke, a dynamics model of free deck run and a dynamics model of fly away. Finally, the optimal combination of the wet steam accumulator was obtained via numerical simulation. The GA method can effectively find the optimal parameters of wet steam accumulator, and its optimized parameters can increase the safety of catapult launch process.